Improving Family-Centered Care for Infants in Neonatal Intensive Care Units: Recommendations From Frontline Healthcare Professionals. (February 2022) - Franck, Linda S.; Bisgaard, Robin; Cormier, Diana M.; Hutchison, Jennifer; Moore, Dishon; Gay, Caryl; Christensen, Holly; Kriz, Rebecca M.; Mora, Jennifer; Ekno, Mary; Hackett, Heather; Lare, Natasha
Abstract : Background: Family-centered care is a philosophy and healthcare delivery model adopted by many neonatal intensive care units (NICUs) worldwide, yet practice varies widely. Purpose: The aim of this study was to synthesize recommendations from frontline NICU healthcare professionals regarding family-centered care. Methods: Data were obtained from the baseline phase of a multicenter quasi-experimental study comparing usual family-centered NICU care (baseline) with mobile-enhanced family integrated care (intervention). Members of the NICU clinical care team completed a family-centered care survey and provided free-text comments regarding practice of family-centered care in their NICU and recommendations for improvement. The comments were analyzed using a directed content analysis approach by a research team that included NICU nurses and parents. Results: Of the 382 NICU healthcare providers from 6 NICUs who completed the survey, 68 (18%) provided 89 free-text comments/recommendations about family-centered care. Almost all comments were provided by nurses (91%). Six main themes were identified: language translation; communication between staff and families; staffing and workflow; team culture and leadership; education; and NICU environment. The need for greater resources for staffing, education, and environmental supports was prominent among the comments, as was team culture and staff–parent communications. Implications for Practice: The NICU healthcare professionals identified a range of issues that support or impede delivery of family-centered care and provided actionable recommendations for improvement. Implications for Research: Future research should include economic analyses that will enable determination of the return on investment so that NICUs can better justify the human and capital resources needed to implement high-quality family-centered care. Abstract : Supplemental Digital Content is Available in the Text.